Structural and morphological investigation of bulk heterojunction blend (NiPc/C60) Thin films under heat treatment - Mkhaiber, Atheer M.; Abdulameer, Ameer F. (Iraqi Journal of Science, 2018)
Thin films of the blended solution of NiPc/C60 are fabricated using spin-coating method for three different ratios (100/1, 100/10 and 100/100) according to the weight. The films are deposited on to glass substrates and treated with several annealing temperatures (373, 423 and 473)K. The structure and surface morphology of the as-deposited and annealed films using x-ray diffraction and AFM was studied and exhibited a change and enhanced crystallization and surface morphology caused by changes in heat treatment temperatures. Investigation of X-ray diffraction patterns of NiPc/C60 indicated that it have polymorphism structure, i.e. mix between amorphous and polycrystalline structure. when heat treatment temperatures changed, led to the α-crystalline films oriented preferentially to the (100) plane. The grain size of the blend (NiPc/C60) thin film is calculated using the Scherrer relation and the variation was nonsystematic with increased annealing temperature. AFM measurements supported the result of XRD.